RITUAL ADAT MA’ACIA DITINJAU DARI PERSPEKTIF PSIKOLOGI INDIGENOUS PADA MASYARAKAT DESA BURANGASI, BUTON SELATAN, SULAWESI TENGGARA - Siti Nuroh (Nusantara: Journal of Cultural Research, 2023)
Ma'acia is a ritual performed when the community has harvested and will open new land, this ritual is one of the hereditary traditions of the Burangasi Village community. This research was conducted to find out how the process of implementing the Ma'acia custom is viewed from the perspective of Indigenous Psychology. The method used in this research is a qualitative method with the type of field research. The data collection is obtained from observation and interviews. The results of this study state that Indigenous Psychology emphasizes the behavior of the community in the local culture, in this case, the behavior is reflected in the habits that are always routinely carried out, namely the Ma'acia traditional ritual. The process of implementing the Ma'acia ritual is carried out in the traditional house of Rumbia, which is always carried out after the main harvest in Burangasi village, this ritual activity is carried out for seven days and seven nights where within this seven-day period, every day there will be singing and dancing accompanied by drum beats as entertainment, because usually this ritual will be attended by many people from other villages who are still of the same tribe as the people in Burangasi Village. The culmination of the Ma'acia ritual on the seventh day will be carried out several activities, namely, eating together, telling historical stories about Burangasi Village, as a series of traditional rituals that cannot be abandoned and continued with a prayer session together as a form of gratitude for the harvest that year.